Efficiency of milk proteins in eliminating practical limitations of β-carotene in hydrated polar solution. (15th November 2020) - Allahdad, Zahra; Varidi, Mehdi; Zadmard, Reza; Haertlé, Thomas; Sawyer, Lindsay; Saboury, Ali Akbar
Highlights: β-Carotene binding to milk proteins enhanced its solubility. Photo and chemical stability of β-carotene increased with milk proteins. Whey proteins was more effective than caseins in reducing of β-carotene aggregates. Milk proteins improved hydrogen transfer property of β-carotene to radical species. Milk proteins diminished electron transfer property of β-carotene to radical species. Abstract: The objective of this work was to study β-carotene functionalities (color and antioxidant activity) and practical limitations (aggregate formation, poor solubility and low stability) when included in the aqueous systems containing milk proteins. According to the results, self-association constant of β-carotene in the presence of casein is 1.7-fold of that calculated for WPI. Casein and WPI were capable of conserving β-carotene against chemical oxidation up to 15 and 12%, respectively, at 1:5 M ratio of β-carotene to protein. While, WPI reduced its photodegradation quantum yield from 0.03 to 0.012 compared to 0.017 obtained for casein. A 2.7- and 3.6-fold enhancement in β-carotene solubility was observed in the presence of 1.5 mg/mL of casein and WPI, respectively. The study of β-carotene interaction with proteins showed, on the one hand, a negative effect on electron transfer and, on the other hand, improved hydrogen transfer to the radical species in the solution.